India's environmental policy standoff: reimagining stakeholder engagement spaces. (1st June 2021) - Tambe, S.; French, L.; Wyborn, C.; Scarlett, L.; Defries, R.; Nagendra, H.; Kulkarni, H.; Srivastava, P.; Agrawal, N.K.; Rathore, B.M.S.; Kinhal, G.
Various stakeholders from science, policy and practice aspire to shape public policy. What are the engagement spaces they operate in, and what are the characteristics of these spaces and the implications for effective policy making? The literature on the public policy formulation process in developing countries is sparse, and this study attempts to bridge this gap. We analyzed India's recent environmental policy making engagements using the lens of 'policy spaces'. We found that strong civil society coalitions have successfully 'claimed' the policy making space. Conventional policy making operating in 'closed' and 'invited' spaces is yet to accept this change, resulting in frequent standoffs. However, when policies emanated from the 'deliberative' space, there have been successes as well. The policy development space has consequently become contested, with nature conservation, forest-based livelihoods and corporate interests all staking their claim. To break this impasse, we recommend a graduation from confrontational and authoritative engagement approaches to deliberative arenas.